2004
DOI: 10.1038/nm1096
|View full text |Cite
|
Sign up to set email alerts
|

Tracking metastatic tumor cell extravasation with quantum dot nanocrystals and fluorescence emission-scanning microscopy

Abstract: Metastasis is an impediment to the development of effective cancer therapies. Our understanding of metastasis is limited by our inability to follow this process in vivo. Fluorescence microscopy offers the potential to follow cells at high resolution in living animals. Semiconductor nanocrystals, quantum dots (QDs), offer considerable advantages over organic fluorophores for this purpose. We used QDs and emission spectrum scanning multiphoton microscopy to develop a means to study extravasation in vivo. Althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
417
0
3

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 644 publications
(441 citation statements)
references
References 25 publications
14
417
0
3
Order By: Relevance
“…Both cell lines retained their detectability level in vivo when the quantum dot assignments were switched, indicating that the measured kinetics of each cell line were not biased by the emission wavelength of quantum dots. These data are consistent with prior work showing that behavior of quantum dot-labeled tumor cells and unlabeled cells in vivo are indistinguishable following tail vein injection [13].…”
Section: Simultaneous Monitoring Of Two Populations In the Circulatiosupporting
confidence: 91%
“…Both cell lines retained their detectability level in vivo when the quantum dot assignments were switched, indicating that the measured kinetics of each cell line were not biased by the emission wavelength of quantum dots. These data are consistent with prior work showing that behavior of quantum dot-labeled tumor cells and unlabeled cells in vivo are indistinguishable following tail vein injection [13].…”
Section: Simultaneous Monitoring Of Two Populations In the Circulatiosupporting
confidence: 91%
“…Several studies have shown that multiple-spectra QDs can be used to achieve coincident tracking of multiple tumor cells in vivo using fluorescence emission-scanning microscopy (Gao et al, 2004;. In the central nervous system, microangiography of deep brain blood vessels and nonspecific labeling of brain cells has been achieved following QD injection into arterial blood (Levene et al, 2004;Voura et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, labelling the tumour cells with Qdots also enabled the tracking of metastatic tumour cell extravasation (Voura et al, 2004). The last study also established the safety profile of Qdots in vivo, although extensive safety and pharmacokinetics studies need to be carried out before use in humans given the fact that Qdots are composed of heavy metals (such as Cd), which can induce liver and kidney damage.…”
Section: Nanotechnology and Tumour Imagingmentioning
confidence: 92%